2012
DOI: 10.1063/1.3684244
|View full text |Cite
|
Sign up to set email alerts
|

Particle size dependent hysteresis loss in La0.7Ce0.3Fe11.6Si1.4C0.2 first-order systems

Abstract: Here, we report particle size dependent hysteresis loss in La0.7Ce0.3Fe11.6Si1.4C0.2. Hysteresis loss was getting smaller with reducing the particle size. The reduced ratio can be as high as ∼61% as the sample is ground from bulk into small particles (20-50 μm). Such reduction can be ascribed to the notably increased surface area of sample and the partially removed internal strain and grain boundaries, other than nucleation factors and electronic band structure. Meanwhile, entropy change |ΔS| slightly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…2a). Generally, hysteresis behavior is related to many intrinsic factors [29,30]. For the coupled MnCoGe alloy system, it was reported that both the magnetic field and thermal activation can induce the FOMTs, but the magnetic field is not an effective way to trigger the FOMTs [21,24].…”
Section: Resultsmentioning
confidence: 99%
“…2a). Generally, hysteresis behavior is related to many intrinsic factors [29,30]. For the coupled MnCoGe alloy system, it was reported that both the magnetic field and thermal activation can induce the FOMTs, but the magnetic field is not an effective way to trigger the FOMTs [21,24].…”
Section: Resultsmentioning
confidence: 99%
“…Since irreversibility is the cause of thermal and magnetic hysteresis when cycling MCE samples across the Curie point, its origin can be investigated with dedicated calorimetry experiments. Many results directed on shape and critical sizes of the materials suggested the fundamental role of micro-structure [9] in the hysteresis determination. However, these measurements, which can characterize the MCE properties of a material, provide volume informations, thus they make hard to distinguish between multiple contributions coming from the micro-scale.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction of MCE under comminution or rapidly quenching, accompanied by the spreading of T C of individual grains over a broader temperature interval was observed also in manganites[38], RCo 2 alloys[39] and other compounds.225Magnetocaloric materials exhibiting a first-order transition are more sensitive to changes of their microstructure than materials with second-order PM-FM transitions. As reported by Liu et al[8], the magnetic entropy change of ballmilled LaFe 11.6 Si 1.4 powders strongly decreases as the particle size is reduced from 160 μm (ΔS m = 20 J·kg −1 ·K −1 ) down to 5 μm (ΔS m = 5 J·kg −1 ·K −1 ).230Taking into account degradation of the MCE when particles become smaller than 100 μm (previously reported also for La-Fe-Co-Si fragments[40] and in La 0.7 Ce 0.3 Fe 11.6 Si 1.4 C 0.2 particles[41]), we did not investigate powders finer than 80 μm in this work.…”
mentioning
confidence: 80%